1999
DOI: 10.1001/archinte.159.15.1710
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Educational Program Improves Clinical Outcome Measures in Inner-City Patients With Asthma

Abstract: Our study suggests that an IEP in the treatment of indigent, inner-city patients hospitalized with asthma reduces the need for subsequent emergent care and improves outpatient follow-up in a cost-effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 34 publications
1
41
0
2
Order By: Relevance
“…15,16 Improving patients' ability to use inhalers may help prevent adverse events post-hospital discharge, including hospital readmissions. [17][18][19] Although a handful of randomized trials have demonstrated beneficial effects of hospital-based patient selfmanagement education for asthma, [20][21][22][23] these studies employed multi-faceted, time-intensive interventions that were compared to usual care. While this literature encourages the use of hospital-based education, direction is lacking as to which intervention or component is most effective.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Improving patients' ability to use inhalers may help prevent adverse events post-hospital discharge, including hospital readmissions. [17][18][19] Although a handful of randomized trials have demonstrated beneficial effects of hospital-based patient selfmanagement education for asthma, [20][21][22][23] these studies employed multi-faceted, time-intensive interventions that were compared to usual care. While this literature encourages the use of hospital-based education, direction is lacking as to which intervention or component is most effective.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most evaluated inpatient programs have served adults with mixed success. [4][5][6][7] Of hospital-based programs targeting children, 3 were multifaceted and included provider quality improvement activities, education, and support. [8][9][10] Three other studies, each reaching fewer than 100 children, focused primarily on patient/caregiver education and support in the hospital during the child's stay.…”
Section: Introductionmentioning
confidence: 99%
“…30,32 The education provided by these interventions was multifaceted and included in varying degrees: basic disease information, self-management skills, medication information and trigger control. The education was provided in the outpatient, 25 29 or research staff.…”
Section: Intervention Outcomesmentioning
confidence: 99%
“…36 All of the education was provided to the individual participant except for two of the ED-based interventions 28,35 and an outpatient pharmacist based intervention that utilized group sessions. 26 Several provided more than one session, including Galbreath's telephone plus home visit intervention, 29 all three inpatient interventions, [30][31][32] and all but one of the ED studies. 36 Of the 8 studies that followed ED visits, all but two 28,29 demonstrated absolute reductions post-education (22-89 %) 25,31,36 or relative reductions compared to control (16-59 %).…”
Section: Intervention Outcomesmentioning
confidence: 99%
See 1 more Smart Citation